PERENCANAANSTRATEGIKSEKOLAH DALAM PENGEMBANGAN PENDIDlKAN BERBASIS LUAS BERORIENTASI KECAKAPAN HIDUP DI SMK - Wiyono, Giri; Sunarto, Sunaryo (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The  purpose   of  this   IPTEKS   application   program   is  to  increase school  headmasters'    ability  for  making  the  schoolwork   programs   based strategic   planning    process.    Therefore    headmasters    of   Vocational    Hig School (SMK)  have:  (1) the ability  to conduct  the school needs  analysis,  (2 the ability to formulate  the school  vision  and mission,  (3) the ability  to draw up plans  for school  development,   (4) the ability  to perform  SWOT  analysi (internal   and  external   condition),   (5)  the  ability  to  formulate   the  schoo objective,  (6) the ability  to understand  of the way to formulate  strategy.Methods  used  in Strategic Planning Workshop are lecture,  questionanswer,    demonstration,      group-task,     seminar;    guidance    to    make    th schoolwork   programs   based   a  strategic   planning   process,   and  games   i outbound   training.   Learning   approaches   used   in  this  training   are  adul education  and practice.The  result   of  Strategic  Planning  Workshop can  be  concluded   afollows:   (a)  Participants    have   global   vision   in  technology   and  strategic issues   of   education    as   formulation    and   development    process    of   th schoolwork  programs  for increasing  quality  of education  in each  school.  (b Participants   can  formulate   and  develop  the  schoolwork  programs  based  o strategic  planning  process  oriented  for school needs in the field of life skills (c) Participants  can develop  self-power  as headmasters  who have th transformational   leadership  to implement  the schoolwork  programs  based  ostrategic planning  and can control  the operation  of this program  interatedly.Key words: strategic planning, life skill